A 10-Year Analysis of Complete Uterine Rupture in Pregnant Women with an Intact Uterus: A Multi-Center Cross-Sectional Study in Sichuan, China - Le Zhou; Chuntang Sun; Guolin He; Meng Chen; Xinghui Liu (IMR Press, 2023)
Background: Complete uterine rupture can lead to serious adverse maternal and child outcomes. Uterine rupture is rare, and it can occur in an intact uterus. Methods: We identified patients with intact uterus who encountered uterine rupture between 2010 and 2020 from the medical records of 10 hospitals in Sichuan Province. Results: In total, 37 cases of uterine rupture in intact uteri were identified. Eight ruptures (8/37, 21.6%) occurred before spontaneous labor, 11 ruptures (11/37, 29.7%) occurred during spontaneous labor, and 18 ruptures (18/37, 48.6%) occurred during induced labor. The clinical manifestations of the patients were abdominal pain in 20 cases (20/37, 54.1%), vaginal bleeding in three cases (3/37, 8.1%), and abdominal pain and vaginal bleeding in eight cases (8/37, 21.6%). The rate of hysterectomy/death was significantly higher in patients with more than three previous vaginal deliveries (p = 0.005). In addition, the rate of hysterectomy/death in the spontaneous labor group was significantly higher than that in the induced labor group (p = 0.011). The fetal survival rate in patients with uterine rupture at the uterine horn was significantly higher than that in patients with uterine rupture at the lower uterine segment (p = 0.007). Conclusions: Uterine rupture in an intact uterus was associated with a high hysterectomy rate and high fetal/neonatal mortality rate. For pregnant women with sudden abdominal pain and abnormal fetal heart rate, we should be alert to the possibility of uterine rupture. Induction and augmentation of labor need to be performed with caution to avoid this potential obstetric emergency.